Analisis Pengaruh Sosial Ekonomi Terhadap Partisipasi Kerja Penduduk Lanjut Usia di Kota Semarang - Hendrawan Asadul Sulthon; Evi Yulia Purwanti (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2022)
This study aims to analyze the influence of age, sex, location of residence, marital status, level of education, household expenditure, and status in the household towards the work participation of the elderly population in the city of Semarang. The type of data used is secondary data, namely the micro population data of the elderly in Semarang City taken from Susenas 2018 obtained from the Badan Pusat Statistik (BPS). The analytical method used in this study is binary logistic regression. The results of the study showed that the variables of age, sex, level of education graduating from high school, level of education graduating from Higher Education and status in the household significantly influence the work participation of the elderly population in the city of Semarang. Whereas the variables that did not significantly affect the working participation of the elderly population in Semarang were residence location, marital status, junior high school education level and household expenditure so that these variables did not have an opportunity to influence the working participation of the elderly population in Semarang City.